Evaluation of Ammoniated Wheat Straw in Receiving and Growing Diets - E. R. Schlegel; S. P. Montgomery; J. W. Waggoner; C. I. Vahl; W. R. Hollenbeck; B. E. Oleen; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2014)
Drought conditions in the past have created a shortage of prairie hay and other grass hays that are used as roughage sources for growing beef diets. Ammoniated wheat straw historically has been available for purchase at a lower than prairie hay. Although some research has been conducted using ammoniated wheat straw as a feedstuff for mature cows, little information is available on the use and outcome its inclusion in beef cattle receiving and growing diets. Our objective was to compare the performance outcomes of newly arrived and growing calves fed total mixed rations containing either ammoniated wheat straw, wheat straw, or a traditional blend of prairie hay and alfalfa hay.
Keywords: beef cattle